Applying light for human health: What lighting designers need to know. (August 2021) - Lam, F
As lighting designers, our work impacts people and the environment. Putting human-centric thinking and approaches at the heart of design is the first principle. This paper reflects a personal view on what lighting designers need to know before they can apply professional judgement and claim that their lighting design will improve human health.